First Season of Operation of the TAIGA Hybrid Cherenkov Array - Sveshnikova, L. G.; Astapov, I. I.; Gafarov, A. R.; Garmash, A. Yu.; Gorbunov, N. V.; Grebenyuk, V. M.; Gress, O. A.; Gress, T. I.; Grishin, O. G.; Grinyuk, A. A.; Horns, D.; Ivanova, A. L.; et al. (Bulletin of the Russian Academy of Sciences: Physics, 2019)
The Tunka-133 Cherenkov complex for recording extensive air showers (EAS) collected data over seven winters from 2009 to 2017. The differential energy spectra of all particles was acquired in the 6 × 1015–3 × 1018 eV range of energies over 2175 h. The TAIGA-HiSCORE complex is continually being expanded and upgraded. Data acquired by 30 first-line stations over 35 days during the period 2017–2018 is analyzed in this work. As at the Tunka-133 setup, the primary particle energies above 1015 eV are measured using the density of the Cherenkov light flux at a distance of 200 m from a shower’s axis. Data on lower energies are collected by determining the energy of the light flux near a shower’s axis. This results in a spectrum of 2 × 1014–1017 eV. The combined spectrum for the two systems covers a range of 2 × 1014–2 × 1018 eV.